Ruch Narodowo-Socjalistyczny NSB w Niderlandach i jego koncepcja polityki zagranicznej w latach 1931–1945 - Kołek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The National Socialist Movement in the Netherlands NSB, established in 1931, was the most important collaborating political party in that country during World War II. The movement developed its own concept of foreign policy, which differed from the policy of Nazi Germany. The party aimed at upholding Europe’s dominant position in the world. To achieve that, the European system should be reconstructed and Germany’s leading role within it needed to be acknowledged. Close cooperation of nation-states should form the basis of the continental order. The prospective Dutch national state — “Dietsland” — was to be composed not only of the Dutch people, but also of the Flemish and the Afrikaners. This united country was also supposed to secure its colonial possessions overseas. This concept of foreign policy was maintained during the whole period of the movement’s existence, even though some minor modifications did occur in the meantime.
Keywords: Mussert Anton; faszyzm; holenderska polityka zagraniczna; NSB